(untitled) (Research, Society and Development, 2022)
Venous thromboembolism is the third most frequent acute cardiovascular disease, where women are at greater risk of developing the disease at childbearing age, and pregnant women are at up to five times greater risk of developing it. This study aims to review the literature regarding the use of anticoagulants in the pregnancy-puerperal cycle and related adverse effects. As a methodology, the platforms MEDLINE/PUBMED, SCIELO, Ministry of Health and book were used, which after exclusion and inclusion criteria, resulted in 25 articles and 1 book included in this study. The results obtained showed that prophylaxis and drug treatment in the pregnancy-puerperal cycle are Low Molecular Weight Heparins and Unfractionated Heparins, but the gold standard of treatment is Low Molecular Weight Heparins. And in extreme cases, Vitamin K Antagonists should be used. Previous research has shown that Direct Oral Anticoagulants should be avoided during the pregnancy-puerperal cycle, as there are still gaps in the knowledge of the risks and benefits of using this class.